Rheological Properties of Alkali Activated Fly Ash Slag Cementitious Materials - Shasha LI; Liubei LI; Wei WU; Hu FENG (Kuangchan zonghe liyong, 2024)
This is an article in the field of ceramics and composites. In order to study the early rheological properties of alkali-activated fly ash-slag cementitious system, the composite pastes with different mass ratios of fly ash (FA) to slag (GGBS) and alkaline activator content were prepared. The fluidity and rheological properties of the pastes were tested by mini-cone slump cone, Brookfield DV3T rheometer,respectively. Finally, the hydration exothermic rate of composite pastes with each ratio was tested by isothermal calorimeter. Results show that when FA/GGBS ratio is 3∶7, the fluidity of paste with 4% NaOH content is the lowest. With the increase of FA mass ratio and NaOH molar mass, the fluidity of alkali-activated FA-GGBS cementitious system increased, and the yield stress and plastic viscosity decreased. The growth of FA content decreases the early hydration rate significantly, while the increase of alkali activator content remarkably increases the peak rate of hydration heat release.